Equations for estimating the coffee leaf area index - Favarin, José Laércio; Neto, Durval Dourado; García, Axel García y; Nova, Nilson Augusto Villa; Favarin, Maria da Graça Guilherme Vieira (Pesquisa Agropecuaria Brasileira, 2002)
With the purpose of estimating the temporal variation of the coffee leaf area index (LAI), using a non destructive simple methodology, an experiment was carried out at the Crop Production Department, Escola Superior de Agricultura Luiz de Queiroz, of the Universidade de São Paulo, Piracicaba, SP, Brazil. The Mundo Novo IAC 388-17 cultivar, grafted on the cultivar Apoatã IAC 2258 (15 to 35 months old), was used with a distance between plants of 2.5 m x 1.0 m, where all leaves of two coffee plants were collected, with intervals varying from 60 to 150 days, to measure the leaf area using the LI-COR equipment (model 3100). To obtain the functional relationship between the LAI and different growth variables (plant height, total number and mass of leaves and leaf area) and the canopy architecture (inferior, medium and superior crop canopy area; crop canopy lateral area; inferior, medium and superior canopy diameter; the plant canopy volume; and the first two branches height), a conic shape for aerial plant architecture was assumed. The inferior canopy diameter (first two branches) and the plant height can be used to estimate the coffee leaf area index.